Manipulasi Data Kredit Usaha Rakyat sebagai Modus Korupsi: Studi Kasus Kejati Sumatera Selatan di Muara Enim - Wahyu Khairatunnisa; Anza Ronaza Bangun (Media Hukum Indonesia (MHI), 2026)
This study examines the practice of data manipulation in the distribution of People's Business Credit (KUR) as a mode of corruption, using a case study of the handling by the South Sumatra High Prosecutor's Office in Muara Enim. The KUR, designed as a financing facility to support the empowerment of micro, small, and medium enterprises, is in practice vulnerable to misuse through debtor data manipulation, identity duplication, and the inclusion of fictitious customers. This method results in misdirected financing, incurring state financial losses, and undermining the primary objective of the KUR program as a driver of economic equality. This study uses a normative juridical approach combined with case studies, examining regulations related to KUR financing, corruption regulations, and investigative documents from the South Sumatra High Prosecutor's Office. The results indicate that KUR data manipulation was carried out through collaboration between unscrupulous bank officials and certain parties who exploited weaknesses in the debtor verification system. Deviations occurred from the administrative process, through eligibility assessment, to fund disbursement. These findings demonstrate that the internal oversight system of banking institutions is not yet functioning optimally, while the government's control mechanism for KUR distribution still has gaps. Furthermore, the Muara Enim case demonstrates that corruption in the distribution of People's Business Credit (KUR) not only results in state losses but also hinders the growth of the MSMEs that are supposed to be the beneficiaries..